Community‐led monitoring: a voice for key populations in Zimbabwe - Makoni, Tatenda; Kadziyanhike, Gilton; Mademutsa, Clarence; Mlambo, Martha; Malama, Kalonde (Journal of the International AIDS Society, 2022)
[...]models have had success in Sierra Leone, where, within a year of implementing a community-led monitoring system, HIV testing increased by 85% among men who have sex with men, 100% among female sex workers, 96% among people who inject drugs and 90% among young people; while antiretroviral therapy uptake increased by 93% among people living with HIV [ 7]. Stigma and discrimination negatively impact the quality of life of people living with HIV in various ways, including detracting from mental health and inhibiting access to care [ 8–10]. The community treatment observatory model at ZNNP+ involves recruiting and training self-disclosed community cadres living with HIV to collect data from their peers, coordinate community dialogues, and engage with community leaders and health facilities.